Metabolic manipulation of Taxus canadensis for taxol production - Phisalaphong, Muenduen, author; Linden, James, advisor; Karim, Nazmul, advisor; Murphy, Vince, committee member; Stushnoff, Cecil, committee member (Colorado State University. Libraries, 1999)
In order to enhance taxol production in suspension cultures of Taxus sp., the regulation of biosynthetic pathways of the secondary metabolites have been investigated. The studies on elicitation and signal transduction showed interdependence of the ethylene and the methyl jasmonate (MJ) actions in affecting taxol biosynthetic reactions in Taxus canadensis C93AD. Reproducible results from independent experiments demonstrated complex changes in taxol and 10-deacetyl taxol, which increased in a manner proportional to MJ and ethylene concentrations. Based on the hypothesis of binding between biotic elicitors and receptor proteins on the plasma membrane, a mathematical model to explain the effects MJ and ethylene on the formation of taxol and other taxanes was developed. The inhibitory effect of MJ on taxol production, especially at concentrations greater than 100 μM, was observed and expressed in mathematical terms in the developed model. Taxol production was enhanced about 30 fold over unelicited conditions using 0.5% CO2, 15% O2 and 7 ppm ethylene with 200 μM MJ elicitation eight days after cell culture transfer. From precursor studies, improved taxol production can be obtained by supplementation of potential taxol side chain precursors and acetyl CoA together with MJ elicitation. The different profiles observed between taxol-related taxanes and baccatin Ill-related taxanes during elicitation suggest baccatin III may be either a degradation product of taxol or a product of 10-deacetyl baccatin III. The examination of profiles of taxol and 10-deacetyl taxol with different precursor supplements suggests a direct enzymatic reaction leading from 10-deacetyl taxol to taxol. A multivariable statistical method, Principal Component Analysis (PCA), was used for quality monitoring and fault detection of the experimental data. A correlation matrix demonstrated a positive relationship between ethylene and taxane concentration, strong positive linear relationships between MJ and taxol, 10-deacetyl taxol and baccatin III, and a negative relationship between MJ and 10-deacetyl baccatin III. Finally, extension of the stationary phase of the cell cycle in a semi-continuous culture with total cell recycle showed considerable improvement in productivity of taxol and other taxanes relative to batch culture.
Keywords: Paclitaxel; Taxus